2021
DOI: 10.1080/07317115.2021.1929630
|View full text |Cite
|
Sign up to set email alerts
|

Positive Aspects of Dementia Caregiving During the COVID-19 Pandemic

Abstract: Objectives: This project investigated experiences of caregivers of people living with dementia during COVID-19. We recorded caregivers' perceptions of care before, during, and moving forward from COVID-19, emphasizing positive experiences, coping strategies, creative care adaptation, strengths demonstrated, and benefits of providing care. Methods: Allied health professionals conducted semi-structured interviews with 26 informal caregivers of people living with dementia. We categorized and thematically analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…A few studies focussed on positive aspects of providing care during the pandemic. In an Australian study, carers noted that providing care during the pandemic revealed their inner strength as well as their priorities and values having changed, whilst the relationship between them and care recipients deepened (Tulloch et al, 2021). Being close and spending more time with loved ones was also presented in other studies (Rising et al, 2021;Sriram et al, 2021).…”
Section: Impact On Mental Wellbeingmentioning
confidence: 86%
See 2 more Smart Citations
“…A few studies focussed on positive aspects of providing care during the pandemic. In an Australian study, carers noted that providing care during the pandemic revealed their inner strength as well as their priorities and values having changed, whilst the relationship between them and care recipients deepened (Tulloch et al, 2021). Being close and spending more time with loved ones was also presented in other studies (Rising et al, 2021;Sriram et al, 2021).…”
Section: Impact On Mental Wellbeingmentioning
confidence: 86%
“…Tulloch et al (2021) purposefully only analysed positive experiences however, clearly producing biased ndings. For many carers, engaging with the person with dementia was their only point of face-to-face social contact during the pandemic, generating feelings of loneliness(Hanna et al, 2021;Tam et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research suggests caregiver resilience may moderate how caregivers experience the pandemic 48. Specifically, some caregivers experienced positive aspects of caregiving during the COVID-19 pandemic, for example, forging deeper connections between caregivers and care-recipients 29,49…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that during COVID-19, people with dementia and family carers found new ways to connect which deepened existing relationships. Furthermore, some prioritised self-care and took part in new or creative activities ( Tulloch et al, 2021 ). These conclusions echo findings from this study.…”
Section: Discussionmentioning
confidence: 99%